KEBIJAKAN SURAT KEPUTUSAN BERSAMA 3 MENTERI (SKB 3 MENTERI) SEBAGAI IMPLEMENTASI PLURALISME DAN MULTIKULTURALISME DI INDONESIA - Prima Roza; Muhammad Hafizh Ramadhan; Fajar Ahmadi (Universitas Muhammadiyah Ponorogo, 2021)
Indonesia is rich in diversity. The socio-cultural diversity in Indonesia is relatively abundant. This can be a strength, but at the same time it can also create friction ad conflict in the society. Recently, the government issued a Joint Decree of 3 Ministers (SKB 3 Menteri) in response to the friction. This decree organize dress procedures in the learning process at schools. As a result of this implementation, various responses emerged from the Indonesian people, either agreement or disagreement. Part of the society that may be relevant to this policy are students. This article will study the perspectives of undergraduate students of Bandung Institute of Technology (ITB), especially of the School of Architecture, Planning and Policy Development’s (SAPPK) on the Joint Decree. This article uses quantitative and qualitative methods by distributing questionnaires and interviews to SAPPK’s students. From the results of this study, the researchers are able to see the perspectives and the trends of SAPPK ITB Students towards the SKB 3 Ministerial Policy as a solution to social issues related to diversity. It is hoped that these results can be used as a reference for campus policy makers in overcoming the same problem.